How Universal Adhesive Systems With Nanoencapsulated Flavonoids Improve Long-Term Bonding to Caries-Affected Dentin - Falconi-Páez, Camila; Aldaz, Mayra Alejandra Nuñez; Navarro, Tobia Gastón; González-Vaca, Claudia Carolina; Campos, Lucas Arrais [UNESP]; Davila-Sanchez, Andres; Arrais, Cesar Augusto Galvão (Wiley, 2025)
Objectives: To determine the presence of nano-encapsulated flavonoids and their effect in universal adhesives on resin-dentin bond-strength (μTBS) and nanoleakage (NL) on artificial caries-affected dentin (CAD) after 24-h and 6 months of water storage (WS). Materials and Methods: Artificial CAD was created on the occlusal dentin surfaces of 60 human third molars by a microbiological assay. Nanoencapsulated quercetin (Q) and naringin (N) were incorporated into Prime&Bond Universal (PBU; Dentsply-Sirona) and Single Bond Universal (SBU, 3M ESPE). The adhesive systems with and without (control) flavonoids were applied to the CAD surface, and a 4-mm resin composite block (TPH Spectrum, Dentsply Sirona) was built up and light-cured. Specimens were sectioned into resin-dentin beams (0.8 mm2). The hybrid layer (HL) was subjected to micro-Raman analysis to detect N and Q. The specimens were tested in tension in a universal testing machine at 0.5 mm/min. μTBS and NL tests were performed after 24-h and WS. μTBS and NL data were analyzed using a nonparametric three-way ANOVA test followed by Bonferroni's test (α = 5%). Results: Q and N were detected within the HL. N and Q nanocapsules increased μTBS and reduced NL values after WS. At 24 h, the PBU group showed higher NL values than the SBU group, and the values decreased after WS. Conclusions: Incorporating nanoencapsulated flavonoids may improve the longevity of universal bonding systems applied to CAD. Clinical Relevance: Adhesive restorations incorporating nanoencapsulated quercetin or naringin might be a promising alternative for achieving long-term bonding stability.
Keywords: caries-affected dentin; collagen cross-linking; dental adhesives; dentin bonding; naringin; quercetin